Microwave-induced pyrolysis of waste automotive oil - Su, Shiung Lam (United Kingdom : University of Cambridge, 2012)
This dissertation describes the development and analysis of the use of microwave heating to power a pyrolysis process (termed “microwave pyrolysis”) for the recycling of used automobile engine oil. By pyrolysing the waste oil in a modified microwave oven in the presence of a bed of particulate-carbon as the microwave-absorbent, hydrocarbons (of smaller molecular size than those present in the waste oil) and H2 are generated and these have potential for use as either an energy source or industrial feedstock. The method was examined for its suitability for processing waste oil by investigating the effects of various process parameters on the yields and properties (chemical and physical) of the products formed.